DESIGN AND SIMULATION OF A 2.4 GHz MONOPOLE ANTENNA ARRAYS WITH PARASITIC ELEMENTS FOR WIRELESS COMMUNICATIONS - Kuate , Alain; Essiben, Jean-François (American Journal of Computing and Engineering, 2021)
Purpose: This paper presents the design and analysis of a 2.4 GHz monopole antenna arrays with parasitic elements for Wireless communications using the Finite-Element Method. Methodology: The antenna arrays are constituted of five quarter wave antenna monopoles of section ¶. The selected configuration is the side coupling on a plan of mass out of rectangular copper of form posed on a FR-4 substrate materiel with relative permittivity of 4.4 and the thickness of section ¶. Only the central monopole is fed and the others known as parasitic are in short-circuit position by an effect of mutual coupling. The so-called CST Microwave Studio simulation software is used to simulate the design antenna. Findings: It is shown that this array is directive with high gain. Recommendations: To integrate this antenna arrays into wireless telecommunication systems, future research must be based on reducing its weight and dimensions. The use of printed monopole elements based on metamaterials may be a possible path for this integration.